The influence of smoking on clinical periodontal disease - Hendiani, Ina (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2009)
Periodontal disease has very complex and multi factor etiology. Plaque bacteria is the main cause of periodontal disease and another risk factor that also plays a role is a smoking habit. Cigarette product such as nicotine can influence the development of periodontal disease that can directly and systemically damage the function of PMN cell. The research was conducted by taking a clinical examination on the smoking influence that covers the number of cigarettes and the period of smoking, and kind of cigarette to the worse of periodontal disease, and by measuring the epithelial attachment loss and the bleeding index. The research was conducted to 152 male aged 20-45 years old, comprised 80 smokers and 72 nonsmokers at the Clinic of Faculty of Dentistry Universitas Indonesia, Jakarta. The result of the research showed that smoking gave influence on the worse of the periodontal disease. There was a profound relationship between the smoking period and the number of cigarettes consumed everyday indicated by the epithelial attachment loss. Smoking did not enhance gingival bleeding. The relationship between kinds of cigarette and the gingival bleeding score and the epithelial attachment loss did not show a significant bleeding.